2019
DOI: 10.1111/dom.13818
|View full text |Cite
|
Sign up to set email alerts
|

Switching to insulin glargine 300 units/mL in real‐world older patients with type 2 diabetes (DELIVER 3)

Abstract: Aim To compare the second‐generation basal insulin glargine 300 units/mL (Gla‐300) and first‐generation basal insulins on glycaemic control and hypoglycaemia risk in older adults with type 2 diabetes (T2D). Materials and methods DELIVER 3 was a retrospective observational cohort study of electronic medical records. A total of 1176 older adults (aged ≥ 65 years) with T2D and ≥1 HbA1c value during 6 month baseline and 3 to 6 month follow‐up who switched from basal insulin to Gla‐300 were propensity score‐matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 36 publications
4
42
0
Order By: Relevance
“…Retrospective RWE corroborates a comparable glycemic control and reduced hypoglycemia with second-generation compared with firstgeneration BI analogues [42][43][44][45][46], with potential cost offsets from a reduction in healthcare utilization and hospitalizations [44]. These findings have been observed in both insulin-naïve T2DM populations [45,46] and in participants who switched from another BI analogue [42][43][44].…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…Retrospective RWE corroborates a comparable glycemic control and reduced hypoglycemia with second-generation compared with firstgeneration BI analogues [42][43][44][45][46], with potential cost offsets from a reduction in healthcare utilization and hospitalizations [44]. These findings have been observed in both insulin-naïve T2DM populations [45,46] and in participants who switched from another BI analogue [42][43][44].…”
Section: Methodssupporting
confidence: 61%
“…Results for RWE studies also support the efficacy and safety of second-generation BIs in individuals with T2DM and obesity [42,43,51,52]. For example, in the DELIVER 3 [42], DELIVER Naïve [46], DELIVER Naïve D [45], DELIVER D?, [51] CONFIRM [52] and LIGHTNING [43] studies, the mean baseline BMI of patients was approximately 33-35 kg/ m 2 . Similarly, most patients in the SWITCH 2 double-blind, cross-over study with IDeg versus Gla-100 had obesity, with an mean BMI of 32.2 kg/m 2 .…”
Section: Obesitymentioning
confidence: 78%
See 1 more Smart Citation
“…After 6 months' follow-up, patients treated with Gla-300 had significantly greater reductions in A1C (− 0.52 vs − 1.30; p = 0.003), with more Gla-300-treated patients achieving A1C < 7.0% (21.9% vs 17.4%; p = 0.003) without hypoglycemia [53]. In DELIVER 3, which studied older patients (≥ 65 years) with T2D switching to Gla-300 from first-generation basal insulins (Gla-100 or insulin detemir), A1C reductions were greater/similar with Gla-300, and A1C goal achievement was similar in both cohorts, but Gla-300-treated patients generally had less hypoglycemia (event rate: adjusted rate ratio 0.63, 95% CI 0.53-0.75; p < 0.001) [54]. Post-hoc and real-world analyses offer important insight, especially when addressing the outcomes in the subpopulation of older adults [52].…”
Section: Insulinmentioning
confidence: 98%
“…Data obtained in the DELIVER program [19,21,22,[25][26][27] with comparative data in propensity-matched cohorts show that people with T2DM who switched to Gla-300 from other basal insulin analog regimens improved their glycemic control with fewer hypoglycemia events, confirming and complementing the results of the EDITION registration clinical program [7][8][9]. Particularly, the DELIVER 2 and 3 study showed that switching basal insulins in T2DM people with elevated HbA1c levels to Gla-300 was associated with significantly lower risk of hypoglycemia than switching to other basal insulins (mainly first-generation basal insulin), with comparable glycemic control; the lower risk of hypoglycemia-related, diabetes-related, and all-cause emergency room services translates into lower costs in patients using Gla-300 [22,24].…”
Section: Discussionmentioning
confidence: 99%